Shocks in dense clouds - Guillet, V.; Pineau des Forêts, G.; Jones, A. P. (Astronomy and astrophysics (Berlin), 2007)
Aims.A new multi-fluid approach to the dust dynamics in transverse shocks in dense clouds is presented with the aim of modelling the dust processing in C- and J-type shocks. Methods.We have augmented an existing steady-state shock code to include the effects of an MRN size distribution of grain cores with icy mantles. The dust charge distribution and its evolution is considered in detail and included in the ionization balance. The 2-D grain dynamics are determined, including the effects of grain inertia and charge fluctuations, paying particular attention to the gyration of the charged grains around the magnetic field lines and the feedback of the ionization state on grain dynamics. Results.We find that the critical velocity for C shocks increases with the gas density but that it is only weakly dependent on a high abundance of PAHs and on the photodetachment of electrons by secondary photons induced by cosmic-rays. The detailed dust dynamics in C shocks is shown to comprise two distinct phases: 1) a short gyration phase followed by 2) a long term drift phase. In J shocks only the first gyration phase is present. In C shocks propagating through molecular clouds (nH = 104 cm-3), large grains (≫100 Å) remain coupled to the magnetic field during the second phase. However, a high abundance of PAHs can lead to a shortage of electrons in the gas and the decoupling of large grains in the shock tail. Large grains are decoupled from the magnetic field all through the C shock in high density clouds (nH = 106 cm-3). In all C shocks small grains ($\simeq$100 Å) remain strongly coupled to the magnetic field, whereas very small grains (≪100 Å) are subject to stochastic dynamics. As long as they are charged very small grains remain strongly coupled to the magnetic field but tend to couple to the neutral gas everytime they become neutral. We have investigated the effects of an electric field along the shock direction in C shocks and find that it does not significantly modify the relative velocities between grains. The derived grain dynamics can be used to study dust processing in C and J shocks in dense clouds through the effects of gas-grain and grain-grain collisions.